AB0170 Cytof Analysis of Lip Biopsies from SjÖgren's Subjects Identifies Dysregulated Immune and Non-Immune Cell Subsets. (9th June 2015) - Haskett, S.; Boudaoud, S.; Reynolds, T.; Nocturne, G.; Themeles, M.; Dunstan, R.; Zheng, T.; Mingueneau, M.; Xavier, M.
Abstract : Background: The cellular characterization of the immune infiltrate in exocrine glands from patients with primary Sjögren's syndrome (pSS) has relied so far on methods with low dimensionality. As a result, our knowledge of cellular events taking place in the exocrine glands of these patients is limited. Objectives: In order to quantify cellular variations associated with pathogenesis, we used here highly multiparametric cytometry by time-of-flight (CyTOF) to analyze diagnostic biopsies from patients with pSS and non-pSS sicca controls. Methods: The CyTOF instrument combines single cell analysis used in flow cytometry with mass spectrometry detection of metal-conjugated antibodies. Using a panel of 36 antibodies, cell populations present in heterogeneous cell suspensions were characterized and correlated with clinical parameters. In parallel, paired formalin-fixed, paraffin embedded sections of labial glands from 15 individuals from this cohort were used to examine anatomic relationships between cell subsets identified by CyTOF. Results: We studied 16 pSS patients and 13 non-pSS sicca controls, among which 81% were anti-SSA+, 44% were anti-SSB+, and 63% had a focus score of 1 or more. In addition to confirming the well-characterized presence of CD4 + T cells and B cells in Sjögren's biopsies, this experimental approach revealed several additional pathologic features, among which are: (a) a dramatic accumulation of CD38 ++ CD27 + HLA-DR low cells (up to 50% of glandular B cells); (b) an unexpected abundance of CD8 + T cells showing marks of activation; (c) the upregulation of HLA-DR on epithelial cells in pSS patients with grades ≥3, which constitutes the first direct evidence of a potential pathological contribution of the epithelium using un-manipulated, ex vivo, primary human cells. Conclusions: The CyTOF instrument is a new tool allowing precise determination of salivary gland subsets, which may generate new mechanistic hypotheses on pathogenesis of the disease. Disclosure of Interest: None declared